IMPROVING THE RUSSIAN CHART OF ACCOUNTS IN THE DIGITAL ECONOMY - O. A. Ageeva (Вестник университета, 2020)
The directions of improving the Russian chart of accounts in order to align it with the International Financial Reporting Standards' requirements and ensure its usability in the digital economy for reports online preparing at the official web-sites of companies, using the cloud technologies have been considered. The proposed method of preparing online reporting assumes that accounting entries will be posted on the lines of financial statements after each transaction occurs, which will enable the users to receive the information about changes in the financial statements immediately. Attention has been paid to the issues of financial statements elements estimates regulation directly by changing the accounting plan, but not by counter accounts. The necessity of abandoning the concept of “additional capital” that does not exist in international practice and an account of the same name in the Russian chart of accounts and replacing it with separate accounts to account for share premium and revaluation reserve has been substantiated.